Profile of Medication Error Incidents in the Prescribing and Transcribing Phases of Outpatients at the Pharmacy Installation of Tidore Islands City - Muhammad Subhan A Sibadu; Nur Arizka Bahrudin; Muhammad Zulfian A Disi; Muh Danial Fajri; Liasari Armaijn (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Medication error is one of the most common types of medical errors and can significantly impact patient safety. Such errors may occur at various stages of the medication process,including prescribing, transcribing, dispensing, and administering drugs to patients.Objective: To identify the profile of medication error incidents during the prescribing and transcribing phases in outpatients at the Pharmacy Installation of the Regional General Hospital (RSD) of Tidore Islands City. Method: This study used a descriptive observational design with a cross-sectional approach, focusing on outpatient prescriptions during the period of October to December 2024.Results: A total of 600 prescriptions (23.3%) were found to contain medication errors. In the prescribing phase, 200 prescriptions (7.77%) had errors, mainly due to the absence of the doctor's registration number (SIP) (7.77%) and the patient's body weight (2.33%). In the transcribing phase, 400 prescriptions (15.5%) contained errors, including incorrect dosage (8.94%), route of administration (0.04%), and drug units (14.57%). Conclusion: Medication errors occurred more frequently in the transcribing phase than in the prescribing phase. These findings are expected to serve as a basis for improving the completeness of prescription writing to prevent medication errors and enhance patient safety at the Pharmacy Installation of RSD Tidore Islands City.